On the insecurity of generalized (Rivest-Shamir-Adleman) - advance and adaptable cryptosystem - Isa, M.A.M.; Rahmany, N.N.A.; Asbullah, M.A.; Sathar, M.H.A.; Rasedee, A.F.N. (IOP Publishing, 2019)
This paper explores the security claims of the Generalized (Rivest-Shamir-Adleman) - Advance and Adaptable Cryptosystem, in short the GRSA-AA cryptosystem. In the GRSA-AA design proposal, the public key n is defined as the multiplication of two large prime numbers, while the values of encryption key E and decryption key D are relying on the result of multiplying 2k large prime numbers called N where n divides N. The GRSA-AA claimed that the brute force is necessary to break the cryptosystem even if the integer n was factored. Nevertheless, this paper aims to show that this scheme is insecure once n is factored. The mathematical proof is presented to show that it is easy to generate an alternative value to the private key D without brute-forcing, yet successfully break the system.